Design and Development of Physics Learning Media of Three Dimensional Animation Using Blender Applications on Atomic Core Material - Muhammad Nasir; Rizo Budi Prastowo; Riwayani Riwayani (Universitas Riau, 2018)
The Aims of this study is to design and build a three dimensional animated physics learning media on the atomic core material using blender application for High School Physics learning media for atomic core material is already exist but still in the form of two dimensions, so it less of visualize actual concept. This research used three-stage of development research. The first stage is the design stage of the media by using instructional design model type ADDIE. The second stage is the stage of media development using the blender application. The third stage is the stage of validation and reliability. Respondents amounted to 54 people consisting of 5 experts (Expert), 11 teachers (user experts), 20 teachers (users) and 18 students (users). Aspects assessed are pedagogic, content and technical. Data collection technique is questionnaire. The results showed the validity score of experts 4.515 which means the learning media is valid with very high category. The Cronbach alpha value of the teacher as user is 0.950 and from student as user is 0.889. it indicated that the media is reliable.